A Successful Limb-Sparing Approach in Synovial Sarcoma of The Foot: A Case Report - Triatmoko, Sara Ester; Andinata, Bob; Atmodiwirjo, Parintosa; Ramadan, Mohamad Rachadian; Siburian, Elida Sari; Hidayat, Andika Prasdipta; Jonathan, Elisa; Sudarman, Jesica Putri (The Lingkar Studi Bedah Plastik Foundation and is affiliated with the Department of Plastic Surgery, Faculty of Medicine, Universitas Indonesia., 2025)
Synovial sarcoma, although rare, is commonly diagnosed in patients under 20 years of age. This case presents the case of a 21-year-old female with synovial sarcoma affecting the 1st to 3rd metatarsal and tarsal bones. She underwent extensive tumor resection, followed by fibula free flap. The fibula was reconstructed into an L-shape to provide structural support. A bypass was performed because of compromised blood flow to the first digit, but the digit failed. Skin necrosis occurred after tumor dissection, necessitating a second reconstruction with an anterolateral thigh flap (ALT) after six weeks. At the years follow-up, the reconstruction was stable, and radiation therapy further improved the outcomes. The patient’s gait was satisfactory, with special shoes for weight bearing. This case demonstrates the potential of limb-sparing surgery with free fibula flaps for synovial sarcoma resection, which offers promising functional and psychological benefits.